Damaging micromechanisms in an as cast ferritic and a ferritized ductile cast iron - D' Agostino, Laura (2017)
Mechanical behavior and damaging micromechanisms in Ductile Cast Irons (DCIs) are strongly effected by matrix microstructure (e.g., phases volume fraction, grains size and grain distribution) and graphite nodules morphology peculiarities (e.g., nodularity level, nodule size, nodule count, etc.). The influence of the graphite nodules depends on both the matrix microstructure and the loading conditions (e.g., quasi-static, dynamic or cyclic loadings). According to the most recent results, these graphite nodules show a mechanical properties gradient inside the graphite nodules, with the graphite elements – matrix debonding as only one of the possible damaging micromechanisms. In this work, two different ferritic DCIs were investigated (a ferritic matrix obtained from as-cast condition and a ferritized matrix) focusing on the damaging micromechanisms in graphite nodules due to tensile stress. Specimens lateral surfaces were observed using a Scanning Electron Microscope (SEM) during the tests following a step by step procedure.